Dialogical and Collaborative Practices Promoted by Kimeltuchefes to Articulate Mapuche Knowledge, Knowledge, and Schoolchildren in Mapuche Contexts - Beltrán-Veliz, Juan Carlos (2022)
Introduction. This original article derived from a research project titled Towards Educational Practices to Make Progress in Intercultural Education in Mapuche Contexts. This is a pending challenge. This research was conducted in Mapuche communities in La Araucanía Region. Objective. To analyze the dialogic practices between Mapuche and traditional school knowledge and knowledge from the perspective of the kimeltuchefes located in rural Mapuche contexts. Methodology. The methodological approach is qualitative, framed in grounded theory. The participants correspond to 36 kimeltuchefes (Mapuche people who carry knowledge, wisdom, and experience); the data collection techniques used were in-depth interviews and focus groups. The analysis process was interpretive. Results. The main results indicate that the Mapuche family plays a fundamental role in the education and transmission of their culture to the Mapuche and non-Mapuche students. It was found that dialogue plays an important role in inter-subjective relationships between kimeltuchefes and teachers since it allows the exchange and learning of knowledge, wisdom, and experiences. In this sense, the school must integrate the Mapuche families and include the Kimeltuchefes through learning communities to advance in the construction of an intercultural curriculum through dialogue and collaborative work. In addition, this requires articulated pedagogical practices and the teacher’s role as a reflective mediator, generator of information and knowledge. Conclusions. The knowledge, wisdom, and experiences of the Mapuche educators must be recognized and valued, which, at the same time, must be in constant dialogue with school knowledge through common cultural, educational projects in order to advance towards intercultural education.